Upaya Peningkatan Pemahaman Keluarga Pasien Terhadap Peran Dan Fungsi Perawat Dalam Pemberian Asuhan Keperawatan - Titik Suhartini; Wardatul washilah; Wahyu Nofiyan Hadi (CV. Multi Kreasi Media, 2022)
Abstract: Incomplete nursing documentation can have an impact on the value of law, communication, education and research. Nursing care documentation is an activity of recording, reporting or recording an incident, as well as activities carried out in the form of providing services that are considered important and valuable. The target of this community partnership program is the families of inpatients at Waluyo Jati Hospital, a total of 65 patient families. The implementing team in the PKM program activities consists of 3 (three) people consisting of 1 chief executive and 2 members. The implementation of this activity was also assisted by 5 Hafshawaty STIKes students. The method used in PKM is through counseling and question and answer. The implementation went smoothly and was carried out separately in each inpatient room. The role of room nurses and patient families is very good and cooperative. After counseling, the patient's family is able to understand the role and function of the nurse in providing nursing care and being identified with several patient families can explore, mention again the role and function of the nurse as experienced by the patient's family during the care of their sick family members. The implementation of this community partnership program requires good cooperation with the Waluyo Jati Kraksaan Hospital. The output of this PKM program is a report on the results of the implementation of community service and the development of materials for nursing management courses. Keywords: roles and functions of nurses, nursing care, counseling